Regional and state heterogeneity of monetary shocks in Argentina - Blanco, Emilio (2019)
This paper empirically investigates how economic activity in Argentina at regional and provincial (i.e., state) levels responds to central national monetary policy shocks, as given by a change in the interest rate. Regional heterogeneity of monetary shocks exists in Argentina. At the regional level the long-term effects of increasing the interest rate are negative and statistically significant. At the provincial level, 11 provinces show a negative and significant impact of a shock on the interest rate over employment. However, there are 13 provinces in which the effect is not statistically significant, including the City of Buenos Aires and Buenos Aires Province. Bayesian methods are implemented to study the discrepancies in the impact on different provinces.